(untitled) - Eldred, Gary W. (Hoboken, NJ, 2005)
More than 100 ideas for side-stepping the pitfalls awaiting the first-time home buyer. This easy-to-follow guide geared to first-time purchasers uses a self-contained format to present the home buyer's most common mistakes, the lesson to be learned from those mistakes, and-if feasible-a preventive strategy.
Keywords: House buying,Mua nhà